Analysis of secondary metabolites and antioxidant activities of ethanol extract of Dendrophthoe pentandra (L.) Miq.) in Sapuran, Central Java - Haryono, Sevien Elamaria; Aditiyarini, Dwi; Restiani, Ratih (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Dendrophthoe pentandra (L.) Miq. are known to have the potential for health because they can be used as natural medicines to cure several diseases, including measles, coughs, diuretics, pain relievers, anti-inflammatory medications, as well as wound healing and infections. The local community in Indonesia has believed the health beneficial of tea mistletoe, but the information of its pharmacological activity is still limited. This research was conducted to explore the species and diversity of secondary metabolites of D. pentandra (L.) Miq. found in Sapuran, Wonosobo and its antioxidant activity. Extraction was performed by maceration in 96% ethanol. It is followed by phytochemical screening, determination of total secondary metabolite compounds, and antioxidant activity assay using DPPH. The results of this study confirmed that mistletoe is D. pentandra (L.). Its leaf extract has a yield of 8.76% that contains alkaloids, saponins, tannins, steroids, phenols, and terpenoids. Its total content of flavonoids, tannins, phenols and saponins was, respectively, 48.584 mg QE/g extract, 1.350 ± 0.140 mg TAE/g extract, 1.756 ± 0.171 g GAE/g extract, 4.665 ± 0.142 g SE/g extract. Its ethanolic extract has very high antioxidant activity with an IC50 value of 49.10 ppm. D. pentandra (L.) Miq. of Sapuran, Wonosobo, has great potential to be developed in the pharmacological field.